Qualifications and competencies of high school biology laboratory human resources in Bantul Regency - Aanisah Aulia Zulfaa; Dwi Yuliyanti; Salma Dwi Amanda; Dwi Fita Rusilawati; Much Fuad Saifuddin; Etika Dyah Puspitasari (Universitas Ahmad Dahlan, 2022)
The biology laboratory is vital in providing students with experience in learning biology, so it needs good management with competent human resources. This study aims to determine the profile of the qualifications and competencies of laboratory staff in supporting laboratory management activities by looking at the achievement of duties and responsibilities to support laboratory management activities in SMA Bantul Regency. This research is descriptive research with qualitative and quantitative approach methods. Data collection techniques using interviews, observation, and questionnaires. The results of the descriptive analysis show that the laboratory manager as a whole still does not meet the standards. The application of administrative competence is more dominant than the application of professional competence. School B's biology laboratory management is more optimal than other schools.